Making sense of the cognitive task of medication reconciliation using a card sorting task - Bitan,Y; Parmet,Y; Greenfield,G; Teng,S; Cook,RI; Nunnally,ME (Human Factors, 2019)
OBJECTIVE:: To explore cognitive strategies clinicians apply while performing a medication reconciliation task, handling incomplete and conflicting information. BACKGROUND:: Medication reconciliation is a method clinicians apply to find and resolve inconsistencies in patients' medications and medical conditions lists. The cognitive strategies clinicians use during reconciliation are unclear. Controlled lab experiments can explore how clinicians make sense of uncertain, missing, or conflicting information and therefore support the development of a human performance model. We hypothesize that clinicians apply varied cognitive strategies to handle this task and that profession and experience affect these strategies. METHOD:: 130 clinicians participated in a tablet-based experiment conducted in a large American teaching hospital. They were asked to simulate medication reconciliation using a card sorting task (CaST) to organize medication and medical condition lists of a specific clinical case. Later on, they were presented with new information and were asked to add it to their arrangements. We quantitatively and qualitatively analyzed the ways clinicians arranged patient information. RESULTS:: Four distinct cognitive strategies were identified ("Conditions first": n = 76 clinicians, "Medications first": n = 7, "Crossover": n = 17, and "Alternating": n = 10). The strategy clinicians applied was affected by their experience ( p = .02) but not by their profession. At the appearance of new information, clinicians moved medication cards more frequently (75.2 movements vs. 49.6 movements, p < .001), suggesting that they match medications to medical conditions. CONCLUSION:: Clinicians apply various cognitive strategies while reconciling medications and medical conditions. APPLICATION:: Clinical information systems should support multiple cognitive strategies, allowing flexibility in organizing information.